Effect of thiazide on rates of bone mineral loss: a longitudinal study. Issue 6764 (8th December 1990) - Wasnich, R; Davis, J; Ross, P; Vogel, J
Abstract : OBJECTIVE–To determine the effect of thiazide diuretic drugs on rates of bone mineral loss. DESIGN–Longitudinal, observational study with a mean follow up of five years. SETTING–Hawaii Osteoporosis Center, Honolulu. SUBJECTS–1017 Japanese-American men born between 1900 and 1920, of whom 378 were treated for hypertension (study group) and 639 did not have hypertension (control group). INTERVENTION–Thiazide diuretics were taken by 325 men for a mean of 11.9 years; 53 men took antihypertensive drugs other than thiazides. MAIN OUTCOME MEASURE–Rate of bone loss estimated from serial photon absorptiometric scanning at three skeletal sites (calcaneus, distal radius, and proximal radius). RESULTS–Rates of bone loss at all three sites were significantly reduced among thiazide users when compared with controls. The reductions in loss rate ranged from 28.8% (p = 0.02) (distal radius) to 49.2% (p = 0.0005) (calcaneus) relative to the controls. At all three sites the men taking other antihypertensive drugs had faster loss rates (22.6-43.1%) than those of the controls but the difference was significant only for the distal radius. CONCLUSION–Thiazide diuretics slow the rate of bone loss in elderly men.